2019
DOI: 10.3390/cancers11050707
|View full text |Cite
|
Sign up to set email alerts
|

NF1 Patients Receiving Breast Cancer Screening: Insights from The Ontario High Risk Breast Screening Program

Abstract: Neurofibromatosis Type I (NF1) is caused by variants in neurofibromin (NF1). NF1 predisposes to a variety of benign and malignant tumor types, including breast cancer. Women with NF1 <50 years of age possess an up to five-fold increased risk of developing breast cancer compared with the general population. Impaired emotional functioning is reported as a comorbidity that may influence the participation of NF1 patients in regular clinical surveillance despite their increased risk of breast and other cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In contrast, other tumour mutations occur more frequently in older individuals, such as PIK3CA (targetable with PIK3CA inhibitors), MLL3, CDH1, and MAP3K1 mutations. 41,42,[47][48][49]57,[61][62][63][64][65] As such, the proportion of patients that qualify for the targeted treatment of a specific molecular alteration is determined by age, although it still needs to be investigated whether the effectiveness differs according to age.…”
Section: Breast Cancermentioning
confidence: 99%
“…In contrast, other tumour mutations occur more frequently in older individuals, such as PIK3CA (targetable with PIK3CA inhibitors), MLL3, CDH1, and MAP3K1 mutations. 41,42,[47][48][49]57,[61][62][63][64][65] As such, the proportion of patients that qualify for the targeted treatment of a specific molecular alteration is determined by age, although it still needs to be investigated whether the effectiveness differs according to age.…”
Section: Breast Cancermentioning
confidence: 99%
“…We also identified two women with pathogenic variants in NF1, three women with pathogenic variants in RAD50, and one woman with a pathogenic in MUTYH. NF1 was relatively recently established as a breast cancer susceptibility gene (41,42). Breast cancers in women with NF1 pathogenic variants are typically diagnosed at younger ages, with the highest incidence in women under 40 years of age, and are associated with relatively poor breast cancer survival (42).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that the peak incidence of breast cancer in Asia and the West varies, ranging from between 40 and 50 years in Asia and 60 and 70 years in the West ( 22 - 24 ). Among patients with neurofibromatosis who develop breast cancer, breast cancer is often discovered at a later stage in patients under 50 years of age and it is therefore important to encourage this population of patients with neurofibromatosis to undergo periodic checkups with earlier screenings than the general population ( 25 ). In addition, since it is difficult for patients with several cutaneous neurofibromas to palpate breast masses in a self-exam, these patients should be classified as a high-risk group and should be encouraged to undergo breast ultrasonography or breast MRI early in life ( 18 , 26 ).…”
Section: Discussionmentioning
confidence: 99%